2009
DOI: 10.1080/10888700902955849
|View full text |Cite
|
Sign up to set email alerts
|

There's a Rat in My Room! Now What? Mice Show No Chronic Physiological Response to the Presence of Rats

Abstract: In general, guidelines on housing and care of animals in the laboratory state that rats and mice should not be housed in the same room. Mice may perceive rats as predators. Although one theory says this can cause stress, there is little scientific evidence to support this theory. In the wild, rats and mice usually do not share the same microhabitat, but this appears to be true for most small rodent species. Furthermore, reports of predatory behavior of rats toward mice mainly originate from experimental settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…Previous research indicates that in the laboratory, mice ignore the activity of rats [44], and in the field, rats do not influence the behaviour of wild mice [55]. Nevertheless, in our study, we believe that the presence of the rats may have repelled the mice.…”
Section: Discussioncontrasting
confidence: 54%
“…Previous research indicates that in the laboratory, mice ignore the activity of rats [44], and in the field, rats do not influence the behaviour of wild mice [55]. Nevertheless, in our study, we believe that the presence of the rats may have repelled the mice.…”
Section: Discussioncontrasting
confidence: 54%
“…Adrenal weight is often used as a measure of stress, reflecting degree of chronic stress hormone production [28][30], and the trend in decreased adrenal weight we observed suggests that mice housed more densely were less stressed; however we recognize that changes did not reach statistical significance. Heart rate, another commonly used measure of stress [31][33], decreased as density increased. This observation may indicate that these mice were less stressed.…”
Section: Discussionmentioning
confidence: 99%
“…Heart rate is often used as a measure of stress (Bernberg et al, 2009; Gilmore et al, 2008; Meijer et al, 2009) and was therefore chosen for evaluation in our study. Our results confirm previous studies that demonstrated reduced heart rate with increased housing density (Nicholson et al, 2009; Van Loo et al, 2007).…”
Section: Discussionmentioning
confidence: 99%